Biomechanical Analysis of a New Eight-Strand Suture for Flexor Tendon Repair - Koji Moriya; Yutaka Maki; Hisao Koda; Naoto Tsubokawa (Indian Journal of Plastic Surgery, 2022)
Background The placement of multistrand sutures during flexor tendon repair requires complicated surgical skills; such suturing is difficult. We developed a new, simpler eight-strand suture, which we term the Yoshizu cross-lock. This reduces the numbers of suture passages through the tendons, as well as the numbers of knots. Methods Fourteen porcine flexor tendons were transected and repaired using the Yoshizu cross-lock system; no peripheral sutures were placed. Our system is a modification of the published, exposed cross-lock repair method that employs a 4–0 monofilament nylon two-strand line and two needles. The repaired tendons were subjected to linear, noncyclic load-to-failure tensile testing. The initial gap, the 2-mm gap force, and the ultimate strength were measured. Results The initial gap force was 12.6 ± 5.6 Newtons (N), the 2-mm gap force was 33.9 ± 10.9 N, and the ultimate strength was 70.1 ± 17.0 N. All tendons subjected to Yoshizu cross-lock repair failed due to suture rupture rather than pullout. Conclusions Our biomechanical study revealed that Yoshizu cross-lock repair had sufficient tensile strength but was associated with wide variation in the 2-mm gap load (standard deviation = 10.9 N). This study is clinically relevant, showing that the Yoshizu cross-lock repair combined with peripheral suturing may allow a repaired flexor tendon to withstand the stresses encountered during early active mobilization. This simple eight-strand technique will be particularly useful to surgeons who commonly employ the cross-lock stitch for primary flexor tendon repair following early mobilization.